Author Correction: Optimal SSSC-based power damping inter-area oscillations using firefly and harmony search algorithms (Scientific Reports, (2020), 10, 1, (12437), 10.1038/s41598-020-69319-x) - Naderipour A.; Abdul?Malek Z.; Ramachandaramurthy V.K.; Miveh M.R.; Moghaddam M.J.H.; Guerrero J.M. (Nature Research, 2023)
erratum